Is it illegal to be autistic? : an analysis of whether the rights situation in different jurisdictions is leading to a silent genocide of autistic persons - Gaetano, Alistair Saviour de (Trinity College (Dublin, Ireland). School of Law, 2017)
The aim of this thesis is to investigate a claim made by certain autistic rights activists, that present-day treatment by society of autistic persons amounts to genocide. This is to be viewed especially in conjunction with a specific proposal by activist Nick Walker, that prosecutions under the United Nations' Genocide Convention should be allowed, through a broad interpretation of legal protection mechanisms. This thesis establishes that autistic persons are, in fact, subjected to an ongoing 'war' on autism, stemming from a power dichotomy in which the majority 'neurotypical' body of the population enforces its status quo views of normalcy, against an autistic minority. This is based on perceptions of 'good and bad' and 'right and wrong', also fuelled by an incorrect understanding of autism, as well as social prejudices towards mental disabilities as traditionally defined.
Keywords: Law, Ph.D.; PhD Trinity College Dublin, 2017